Dansk i danske samlinger. Om Udenlandske Danica i det 20. århundrede - Jacobsen, Grethe (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
In the National Collection of printed works in the National Library of Denmark and Copenhagen University Library, primarily collected through Legal Deposit, one finds also works published abroad, dealing with Denmark and Danes, the so-called Danica extranea. These have been collected since 1788 when instructions, written to the new director of the library, ordered him to purchase works dealing with all the Danish states and colonies and their subjects. At that time the Danish king ruled over Denmark, Norway, the Duchies (Schleswig-Holstein) as well as colonies in India, Africa and the Caribbean. This kingdom was reduced 26 years later following the Treaty of Kiel in 1814 when Norway was ceded to Sweden. In 1864, the Duchies became part of the emerging German Empire. According to the instructions of 1788, this should also have influenced the acquisition of Danica extranea. However, this was not the case. The staff of the Danish Department (established in 1780) of the library retained until 1991 the image of Denmark as it had been before 1814 when it came to defining what should be purchased for the national collection. The article describes how this was formulated and carried out in practice during the second half of the twentieth century. The Department operated with three categories of Danica extranea: extranea proper, non-extranea (works on areas and people who had at one point in time belonged to Denmark or had been Danish subjects), and Scandinavica (works on Scandinavian countries and people, unless dealing exclusively with Sweden). This was confusing for people using the library, for example they had to look for Norwegian books published after 1814 in the Danish catalogue and not in the foreign, catalogue, and it created internal conflicts in the library when books purchased for general circulation were withheld in the national collection because of their subject matter and then could only be used in the Reading Room. The issue was resolved in 1991 when acquisitions of non-extranea and Scandinavica became the task of the University Department and purchases of duplicate copies was made possible in case of any conflict. The introduction of an online catalogue in 1998, into which all separate card catalogues were merged made it easier for users to find a book.